MODEL PENGEMBANGAN KARAKTER MELALUI PENDIDIKAN SENI DI SEKOLAH DASAR - Ardipal, Ardipal (Humanus, 2015)
Character building is the main focus of Curriculum 2013. However, this effort is almost replaced by the program of mental revolution â€œrelaunchedâ€ by Joko Widodo in his campaign and it has been one of his programs today. Arts education is often underestimated; in fact, it has a major role in shaping the character of the nation. Therefore, this research aims to identify problems in character building of Indonesiaâ€™s human resource through arts education. Research findings show that teachersâ€™ concept on art education in elementary schools is one of the factors that influence the success of the Cultural Arts learning at the elementary level. Currently, most teachers view that art education includes activities to make students sing, draw, and/or make crafts at early age. This understanding is needed to be revolutionized as Curriculum 2013 mandates changes in concepts and patterns of learning for the good characters of the next generation, such as independent, good natured, and ready to face the future. Furthermore, it describes and identified the problems encountered in learning the art of music in elementary school, which underlies the need for arts education in mental revolution of the young generation as a potential future leaders.Keywords: art education problems, character building, elementary school, Curriculum 2013